(untitled) (Research, Society and Development, 2021)
In the presente article will be analized the means by which the legal act may acquire the stability, that are the stabilization, preclusion and res judicata, so that will be defined the difference between these three institutes, as well as the importance of the stability of the legal act for the brasilian civil procedural order will be studied, the relevance of the principle of stabilisation of judicial decisions and aspects of the Rescission Action, its legal nature and its hypotheses of application described in the tax roll of the procedural legislation, especially with regard to the impact of such action on the stabilisation of judicial decisions in order to examine whether or not the Rescission Action breaks the security and stability expected of the legal act, it is verified also that the rescission action is endorsed with importance because it protects the legal system and also corrects injustices, concluding that there is no need to speak of an affront to legal security.